Thor. Love and thunder [videorecording (Blu-Ray)] - Waititi, Taika; Waititi, Taika; Robinson, Jennifer Kaytin; Hemsworth, Chris; Bale, Christian, 1974-; Thompson, Tessa, 1983-; Alexander, Jaimie; Crowe, Russell, 1964-; Portman, Natalie, 1981-; Pratt, Chris, 1979-; Bautista, David, 1969-; Gillan, Karen, 1987-; et al. (Marvel Studios, 2022)
Thor enlists the help of Valkyrie, Korg and ex-girlfriend Jane Foster to fight Gorr the God Butcher, who intends to make the gods extinct.